Guidelines for Creating Cooperation in Disaster Prevention and Relief in the Area of Kok Raet Subdistrict Administrative Organization Kong Krailat District Sukhothai Province - Pliandee, Patcharapon; Bodeerat, Chot; Phongrod , Yuvadee (Journal of Graduate MCU KhonKaen Campus, 2025)
This independent study aimed to 1) study the level of disaster prevention and mitigation in Kok Rat Subdistrict Administrative Organization, 2) compare personal factors affecting disaster prevention and mitigation in Kok Rat Subdistrict Administrative Organization, and 3) propose guidelines for establishing a cooperation network for disaster prevention and mitigation in Kok Rat Subdistrict Administrative Organization. The research was conducted according to the mixed methodology of quantitative research and qualitative research. The population and sample consisted of 308 people and 7 key informants. The research tools were questionnaires and interview forms. Data were analyzed using statistics, frequency, percentage, mean, standard deviation, t-test, F-test, and descriptive data analysis. The research results found that. 1) The overall of disaster prevention and mitigation in Kok Rat Subdistrict Administrative Organization was at a high level. 2) The comparison of personal factors and opinions on disaster prevention and mitigation in Kokrat Subdistrict Administrative Organization, found that people with different genders, ages, education, occupations, average monthly incomes, and length of stay in the area had no different opinions on disaster prevention and mitigation. Therefore, the hypothesis was rejected 3) The guidelines for establishing a network of cooperation in disaster prevention and mitigation inKokrat Subdistrict Administrative Organization, could be summarized as a model, namely the Patcharapon Model, which was a model of the process of establishing a network of cooperation in disaster prevention and mitigation, consisting of the following processes: 1) Perception, 2) Vision, 3) Interaction, 4) Participation, 5) nterdependent and 6) Benefits.